PERAN DALIHAN NA TOLU DALAM MENYELESAIKAN PERMASALAHAN KEKERASAN DALAM RUMAH TANGGA (KDRT) DI KABUPATEN HUMBANG HASUNDUTAN - Lumbanbatu, Herlina; Hidir, Achmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Dalihan na tolu is the one of tradition in batak toba society that cannot be separated. In batak toba family, Dalihan na Tolu has set detailed rules and regulations about social relation among husband and wife, parents between siblings from each party. The problem that will be discussed in this thesis is about the role of Dalihan na Tolu in solving the problem of domestic violence in district of Humbang Hasundutan according to common law of Batak Toba and the form of penalty given by Dalihan na Tolu to figure that carry out domestic violence. The subject in this research there are three of tradional figures, also three pairs of husband and wife who have experienced in domestic violence and has been settled based on customary law. The research method of this research is use purposive sampling and use qualitative descriptive method. This theory is authority theory panopticone was found by Michael Foucault. The result of this research shows that Dalihan na Tolu very concern about cooperation between roles of element Dalihan na Tolu itself there are: dongan tubu, hula-hula and boru. It also cannot be separated from significance of the saying of Dalihan na Tolu which said â€œsomba marhula-hula, manat mardongan tubu, dan elek marboruâ€ the words have deep meaning and absolutely must do if want to have prosperous life. In Batak Toba society, the leader in group of Dalihan na Tolu can be said to be a mediator in resolving the problem of domestic violence, because the leader becomes the party involved between the parties that are experiencing conflict to then resolve the issue between the two problematic parties, where a peaceful solution is very prioritized. The form of sanctions that can be in the form of payment of compensation to the victim and also the obligation to pay all costs incurred when the problem is resolved by customary law other than that other sanctions are the obligation to apologize to the victim and witnessed by all parties who participated in the settlement.Keywords: Dalihan na Tolu, Domestic Violence, Batak Toba.